2021
DOI: 10.1186/s12889-021-10787-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to test the effect of simplified guidance with visuals on comprehension of COVID-19 guidelines and intention to stay home if symptomatic

Abstract: Background In the COVID-19 pandemic, it is imperative that people understand and comply with self-isolation guidelines. We tested whether a simplified version of the guidelines and a simplified version with visual aids would affect comprehension and intention to self-isolate during the containment phase of the pandemic in the UK, in March 2020, compared to the standard guidelines. Methods We conducted an online, three-armed parallel randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In the COVID-19 pandemic, rapid large-scale online surveys were used to establish attitudes and intentions towards planned or ongoing interventions, such as testing, self-isolation and vaccination ( 25 , 26 ). Experimental online evaluation (such as A:B testing) of the likely impact of messages on attitudes and intentions was used to test their relative effectiveness and to modify the messages accordingly ( 27–29 ). For example, an online experiment found that adding a single sentence informing participants that there was still a chance that they could be infectious significantly improved participant understanding of the risk of transmitting COVID-19 following a negative test result ( 30 ).…”
Section: Rapid Mixed Methods Evaluation Of Interventions and Messagesmentioning
confidence: 99%
“…In the COVID-19 pandemic, rapid large-scale online surveys were used to establish attitudes and intentions towards planned or ongoing interventions, such as testing, self-isolation and vaccination ( 25 , 26 ). Experimental online evaluation (such as A:B testing) of the likely impact of messages on attitudes and intentions was used to test their relative effectiveness and to modify the messages accordingly ( 27–29 ). For example, an online experiment found that adding a single sentence informing participants that there was still a chance that they could be infectious significantly improved participant understanding of the risk of transmitting COVID-19 following a negative test result ( 30 ).…”
Section: Rapid Mixed Methods Evaluation Of Interventions and Messagesmentioning
confidence: 99%
“…[16,17] Experimental online evaluation (such as A:B testing) of the likely impact of messages on attitudes and intentions was used to test their relative effectiveness and to modify the messages accordingly. [18][19][20] For example, an online experiment found that adding a single sentence informing participants that there was still a chance that they could be infectious significantly improved participant understanding of the risk of transmitting COVID-19 following a negative test result. [19] Online studies evaluating perceived importance of mitigation measures among individuals attending cultural events informed implementation of infection control polices at mass events.…”
Section: Rapid Mixed Methods Evaluation Of Interventions and Messagesmentioning
confidence: 99%